Anisotropic charge transport study of highly oriented P4T2F-HD thin film fabricated at air-liquid interface through second harmonic generation (SHG) analysis - Shyam R.; Manaka T.; Prakash R. (My University, 2025)
This study delves into the anisotropic carrier transport characteristics of unidirectionally aligned films made from poly(4-terthiophen-2-yl-difluorobenzothiadiazole) (P4T2F-HD) by using time-resolved microscopic optical second-harmonic generation (TRM-SHG) imaging. Utilizing the unexplored polymer P4T2F-HD for the first time, we focus on exploring its distinctive molecular orientation. This approach provides a unique opportunity to study charge transport dynamics with exceptional spatial and temporal precision within this material. Through SHG imaging, we can directly capture the directional dependency of carrier mobility within the films, uncovering a significant anisotropy in electronic transport. Our methodological approach enabled the visualization of charge movement in real-time, enabling quantitative assessments of carrier velocity and diffusion along distinct directions. The outcomes reveal a marked directional preference in carrier transport, which can be attributed to the molecular orientation and packing within the P4T2F-HD films. This anisotropy is meticulously analyzed in light of the material's electronic structure and molecular orientation, providing a thorough understanding of the forces propelling charge transport in organic semiconductor materials. © 2024 RSC.